Patients' and Clinicians' Views of the Psychological Components of Tinnitus Treatment That Could Inform Audiologists' Usual Care: A Delphi Survey. Issue 2 (March 2018) - Thompson, Dean M.; Taylor, John; Hall, Deborah A.; Walker, Dawn-Marie; McMurran, Mary; Casey, Amanda; Stockdale, David; Featherstone, Debbie; Hoare, Derek J.
Abstract : Objectives: The aim of this study was to determine which components of psychological therapies are most important and appropriate to inform audiologists' usual care for people with tinnitus. Design: A 39-member panel of patients, audiologists, hearing therapists, and psychologists completed a three-round Delphi survey to reach consensus on essential components of audiologist-delivered psychologically informed care for tinnitus. Results: Consensus (≥80% agreement) was reached on including 76 of 160 components. No components reached consensus for exclusion. The components reaching consensus were predominantly common therapeutic skills such as Socratic questioning and active listening, rather than specific techniques, for example, graded exposure therapy or cognitive restructuring. Consensus on educational components to include largely concerned psychological models of tinnitus rather than neurophysiological information. Conclusions: The results of this Delphi survey provide a tool to develop audiologists' usual tinnitus care using components that both patients and clinicians agree are important and appropriate to be delivered by an audiologist for adults with tinnitus-related distress. Research is now necessary to test the added effects of these components when delivered by audiologists. Abstract : Supplemental Digital Content is available in the text.